Pengaruh Struktur Modal dan Keputusan Investasi terhadap Kinerja Keuangan Perbankan dengan Corporate Governance sebagai Pemoderasi - Mohamad Rio Aditya Lutfiansyah; Nera Marinda Machdar (UNIVERSITAS KALBIS, 2022)
This study at to determine the impact of capital structure and investment decisions on financial performance, both with and without corporate governance as a moderator. The population consisted of all banks listed on the Indonesia Stock Exchange (IDX) between 2014 and 2018. Saturated sampling was used to select the sample, which comprised 45 banking institutions and 225 observations. Using version 25 of SPSS, multiple linear regression analysis was used to analyze the data. The results indicated that DER had no impact on ROA, NPL, or LDR, but had a negative impact on ROE. TAG has a positive effect on NPL but no effect on ROA, ROE, or LDR. RCE/BVA has no effect on monetary performance. Managerial ownership moderates the DER for ROA and NPL, but not for ROE and LDR. TAG and RCE/BVA on ROA are moderated by managerial ownership, but ROE, NPL, and LDR are not. Institutional ownership has no impact on the relationship between capital structure and financial performance.